The Europa directory of international organizations 2005. (Routledge, 2005)
A one volume guide to over 1,800 international and regional organisations. Each entry contains, where applicable, contact information, details of membership, principal officers, activities, finance, publications. Includes international observances; texts of significant international charters, treaties; key UN Security Council and General Assembly resolutions; historical development of international organizations, who's who in international organizations.